Development of mechanization of dairy cattle rearing in Russia and the Soviet Union in the first half of the twentieth century - V. F. Vtoryi; S. V. Vtoryi (Аграрная наука Евро-Северо-Востока, 2024)
The study aimed to look into how dairy cattle rearing in Russia and the USSR got technical and technological support in the first half of the twentieth century. At the start of the 20th century, two-thirds of Russian agriculture were small peasant farms. They used manual labor and did not need the costly machines. The consolidation of farms was very slow. Yet it laid the foundation for a shift to mechanized livestock production. The First World War, which began in 1914, followed by the Revolution and the Civil War halted for years the technical development of Russia's agricultural production. In late 20s, the Soviet Union already faced the challenge of producing more agricultural goods. This increase could be possible by starting highly mechanized agricultural enterprises. By 1931, “Soyuzselstroy”, an All-Union Agricultural Construction Association, had prepared standard designs of dairy cattle farms for 100 and 200 heads. They provided for mechanization of main processes of cow housing and care. In 1930-1940, scientists and engineers of the All-Union Institute of Mechanization (VIM) and its branches undertook the creation of cattle farming machinery. This period saw the development and manufacture of a number of machines that made livestock farmers labor easier. The work on setting standards for designing the cow barns started. By 1939, VIM had designed a system of machines and test edit in collective farms. The need for specialized organizations to help collective farms to install and put into operation the livestock equipment became evident. At the same time, training of agricultural engineers started in Leningrad, Moscow and other USSR cities. A Decree by the Council of People's Commissars of the Soviet Union dated July 8, 1939, set a delivery plan of machines and units for livestock farming in 1940. Thus, by 1941 the conditions were created for integrated mechanization of main labor-intensive processes in national animal husbandry. Those days agricultural ecology was not in the focus. With no widespread production of mineral fertilizers in place, application of all manure to soil posed no environmental risk.